Development of smart plasma antenna by using fluorescent tube for wireless communication application / Hajar Ja'afar ... [et al.] - Ja'afar, Hajar; Abdullah, Rina; Ismail, Nuraiza; Shafie, Rosmawati; Omar, Suziana; Rustam, Ilham (2017)
Plasma antenna is a general term that represents the use of ionized gas as a conducting medium instead of a metal to either transmit or reflect a signal to achieve radar [2-3], or stealth or communication purpose [4]. There are many ways to generate plasma medium as a conductor element such as UV laser irradiation, or by laser initiated pre-ionization or by simply using commercial fluorescent lamp as a plasma antenna. In this work the commercial fluorescent lamp was chosen because it was low cost to produce plasma element. This research study the performance of plasma antenna using a single fluorescent tube and reviews the antenna performance as a transmitter and receiver. The main objective in this research is to design plasma antenna based on plasma medium by using commercially available fluorescent tube for wireless communication application. A typical fluorescent lamp consists of a glass tube with its inner surface coated with fluorescent powder. It is filled with mixture of argon gas and mercury vapour. When the gas inside the tube is energize by RF signal, the gas inside the tube will convert into plasma state and capable to transmit and receive radio signal with the help of coupling sleeve. As a comparison to the plasma antenna proposed in the literature review previously, the plasma antenna in this study was made from cylindrical shaped fluorescent lamp that functioned as a radiating element with target frequency at 2.4 GHz for Wi-Fi application. In this project using plasma antennas instead of metallic elements. When a plasma element is not energized (OFF), the tube will convert the plasma back to a normal gas state, which significantly reduced its radar cross section. Even when it is energized (ON), it is transparent to the transmission above the plasma frequency, which falls in the microwave region. Plasma elements can energize and de-energized in seconds which is can prevent from radar detection. So the possibility to switch on and off the plasma makes plasma antennas suitable for the production of time varying radar cross section elements. Conventional metal antennas are unable to hide from enemy radar even if turned off, since they are still conductors which reflect electromagnetic waves.